Analisis Sifat Fisik Tanah Lokasi Penanaman Bawang Merah di Daerah Tangkapan Air Danau Toba - Adven Bangun Simanungkalit; Razali Razali; Posma Marbun (Universitas Sumatera Utara, 2019)
ABSTRACT Soil's physical properties are one of the factors that influence the productivity of shallots. This research aims to determine the correlation of soil's physical properties towards productivity of shallots in Watershed of Lake Toba. This research was carried out in the center of the shallot planting area in the area of ​​Lake Toba, Muara District, Bakti Raja District, Silahisabungan District, Merek District, Haranggaol District, and Samosir Island, which have at altitude 911 – 1432 meters above sea level. This research used survey methods which includes literature studies, preparation of the questionnaire, survey around of Lake Toba and processing data from survey in Lake Toba area. The results showed that soil's physical properties and the productivity of shallots had a correlation with value of r = 0.71. The best soil texture for the cultivation of shallots in Watershed of Lake Toba is sandy loam. Keywords : shallots, soil's physical properties, Watershed of Lake Toba